The story of the integration of the Indian States - Menon, V. P. (Orient Blackswan, 2019)
V.P. Menon worked closely with Sardar Patel to help integrate the princely states with India. The book details the negotiations he carried out with each of these states. ... It tells us how the process of carving out states from the jigsaw puzzle that India was after Independence is something that continues.